High Current Pulse Transducer for Metal-Oxide Surge Arresters - Gurevich, V. (Електротехніка і електромеханіка, 2007)
High-voltage arresters of 160 kV and higher voltage types based on zinc-oxide varistors are important and expensive devices. The main imperfection of existing devices for the varistors monitoring is necessity of human intervention to work with them. A simple automatic high-current pulse transducer included in SCADA system by means of a radio transmitting- receiving set and intended for the arresters control is introduced. Високовольтні розрядники класу 160 кВ і вище на основі оксидно-цинкових варисторів є відповідальними і дорогими апаратами. Головним недоліком відомих пристроїв для моніторингу варисторів є необхідність участі людини в роботі з ними. Запропонований простий, повністю автоматичний датчик імпульсних струмів для контролю розрядників, включений в систему SCADA за допомогою комплекту радіопередавач-приймач. Высоковольтные разрядники класса 160 кВ и выше на основе оксидно-цинковых варисторов являются ответственными и дорогостоящими аппаратами. Главным недостатком известных устройств для мониторинга варисторов является необходимость участия человека в работе с ними. Предложен простой, полностью автоматический датчик импульсных токов для контроля разрядников, включенный в систему SCADA посредством комплекта радиопередатчик-приемник.